MINERAL INCLUSIONS IN MICRODIAMONDS AND MACRODIAMONDS FROM KIMBERLITES OF YAKUTIA: A COMPARATIVE STUDY - Sobolev N.V.; Logvinova A.M.; Zedgenizov D.A.; Seryotkin Y.V.; Yefimova E.S.; Floss C.; Taylor L.A. (My University, 2004)
Chemical compositions were determined onmineral inclusions recovered from 290microdiamonds ( < 1mm) from 8 operating diamond mines in Yakutia. The sampled diamond mines include Mir, Udachnaya, Internatsionalnaya, Aykhal, Sytykanskaya, Yubileynaya, Komsomolskaya and Krasnopresnenskaya. The mineral inclusions include both ultramafic (peridotitic) suite (Utype) and eclogitic suite (E-type) examples. Olivines, chromites, Cr-pyropes, Cr-diopsides and enstatite were studied from U-type diamonds. Mg–Ca–Fe-garnets and omphacitic clinopyroxenes were studied from E-type microdiamonds. Abundances and compositions of these inclusions were compared with published and unpublished data on inclusions available from approximately 2000 macrodiamonds (>1 mm) from the same sources, and worldwide data for olivines and chromites. Although there are general similarities, notable exceptions were detected in about 10% of the inclusions from microdiamonds. For each of the pipes, anomalous compositions occur between the microand macrodiamond inclusions, but in different proportions, sometimes as high as 50% of the inclusions. Our study has demonstrated that mineral inclusions in microdiamonds are considerably more variable in their compositions and parageneses compared with inclusions in macrodiamonds. Significant compositional anomalies in inclusions frommicrodiamonds include: (1) garnets containing pyroxene solid solution (majoritic component) both in Uand E-type microdiamonds from three pipes: Yubileynaya, Komsomolskaya and Krasnopresnenskaya. The moles of Si (pfu) in these garnets range from 3.07 to 3.13 and as high as 3.29, on the basis of 12 oxygens, along with a notable contents of Na2O in two eclogitic garnets (0.43 and 0.93 wt.%) and uniquely high Cr2O3 and CaO contents in an ultramafic garnet of wehrlitic paragenesis; (2) coexisting wehrlitic garnets in a single microdiamond, one majoritic, the other normal, both with distinct + Eu anomalies, considered as signatures of crustal protoliths for the precursors to these garnets; (3) olivines with relatively low Fo (86–89) and high-NiO contents (0.46–0.64 wt.%), from Yubileynaya and Sytykanskaya microdiamonds; (4) chromites containing high-TiO2 (up to 4.7 wt.%) and some extremely rich inMgO (Mg# 80). It is concluded that many of these compositional features observed may be related to a deeper origin for the microdiamond source region (>300 km), for at least a 10–30% portion of microdiamonds from each Yakutian pipe.